Improving technology acceptance modelling for developing communities using a systems engineering approach. (1st January 2013) - Sarkani, Shahram; Mazzuchi, Thomas A.; Fletcher, Jordan
Developing nations are poised to spend billions on ICT innovation in 2020. A study of the historical adoption of ICT in developing nations indicated that their adoption patterns do not follow typical technology innovation adoption models. This study addressed the weaknesses found in existing technology acceptance models and proposed a new technology acceptance modelling approach and conceptual model. The new model integrated the population and technology characteristics factors found in popular technology acceptance models to task and process factors found in other models, consistent with enterprise system engineering principles and the Information Technology Infrastructure Library framework. This study also addressed the weakness in the survey approach by introducing data from publicly-available industry and economic data sources. An experiment was conducted on 42 nations in Sub-Saharan Africa, resulting in validation of the model. This new model and approach should be further validated by future research.